Edukasi dan Pendampingan bagi Petani Sawit Rakyat dalam Proses Pembibitan Kelapa Sawit dengan Alternatif Media Tanam Sekam Padi dan Tanah Top Soil - Delyana Rahmawany Pulungan; Makhrani Sari Ginting; Parinduri Sulthon; Muhammad Abrar Parinduri (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2022)
The quality of the planting media affects the quality of oil palm plant growth because in the mini tan media there are important nutrients that support plant growth. One of the planting media that contains good nutrients for oil palm seedlings is rice husk charcoal with top soil soil. This planting medium is an effective alternative at a low price and easy for smallholder oil palm farmers to use in plantation areas for oil palm seedlings. The low literacy of smallholder oil palm farmers in the plantation area makes these service partners not aware of several alternatives in cultivation due to the low level of access to information about cultivation with various alternatives provided by nature. This service activity aims to provide education and increase partner literacy in the use of rice husk and top soil planting media as planting media for easy and inexpensive oil palm seedlings to support plant quality. Partners are very happy and give a positive response with active discussions in the entire empowerment process from introduction, education to assistance in trials of making the planting media